Robotic-enhanced hybrid ablation for persistent and long-standing atrial fibrillation: Early assessment of feasibility, safety, and efficacyCentral MessagePerspective - Stefano Schena, MD, PhD; Jacob Lindemann, BS; Anne Carlson, RN; Trisha Wilcox, ANP; James Oujiri, MD; Marcie Berger, MD; Mario Gasparri, MD (JTCVS Techniques)
Objectives: To assess feasibility, safety, and early efficacy of robotic-enhanced epicardial ablation (RE-EA) as first stage of a hybrid approach to patients with persistent (PsAF) and long-standing atrial fibrillation (LSAF). Methods: Single-center, retrospective analysis of patients with documented PsAF and LSAF who underwent RE-EA followed by catheter-guided endocardial ablation. Postoperatively, patients were monitored for major adverse events and underwent rhythm follow-up at 3 and 12 months. Results: Between January 2021 and June 2023, we performed RE-EA in 64 patients (73.5% male, CHA2DS2-VASc 2.7 ± 1.6, BMI 34.1 ± 6.3 kg/m2). Mean AF preoperative duration and left atrial volume index were, respectively, 85 months and 47.5 mL/m2. Through the robotic approach, the intended lesion set was completed in all patients without cardiopulmonary bypass support, conversion to thoracotomy/sternotomy, blood transfusions, or perioperative mortality. The average LOS was 1.7 days, with only 1 patient requiring intensive care unit admission and >65% of patients discharged within 24 hours. At follow-up, 2 (3.1%) patients experienced new left pleural effusion or hemidiaphragm paralysis requiring treatment. There were no readmissions related to AF, stroke, thromboembolic events, or deaths. The mean interval between the epicardial and endocardial stages of the procedure was 5.9 months. Rhythm follow-up showed AF resolution in 73.4% and 71.9% of patients at 3 and 12 months, respectively. Conclusions: RE-EA is a feasible and safe, first-stage approach for the treatment of patients with PsAF and LSAF. It improves exposure of the intended targets, favors short hospital stay, and facilitates return to activity with satisfactory AF treatment in the short term.